Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Dinas XYZ di Kabupaten Tebo - Mayroza Wiska; Fenisi Resty; Eka Ermawati; Uliya Uliya (Universitas Batanghari, 2022)
The purpose of this study was to determine and analyze the effect of work motivation and work discipline partially and simultaneously on employee performance. The type of research in this study is associative with the form of a causal relationship, using this research approach with quantitative methods. The results showed that work motivation had a significant effect and had a positive direction on employee performance. Work discipline has a significant effect and has a positive direction on employee performance. Work motivation and work discipline simultaneously have a significant effect on employee performance. The result of the coefficient of determination is known that the contribution given by work motivation and work discipline to employee performance is 210 while the remaining 458 is influenced by other variables not examined in this study. So disciplined motivation and work discipline partially and simultaneously affect employee performance and have a positive relationship direction